A COMPARATIVE STUDY OF LANGUAGE DEATH IN ENDANGERED LANGUAGES (Ta'limning zamonaviy transformatsiyasi, 2025)
ABSTRACT: Language is fundamental to our existence; it allows us to distinguish between people and animals and helps us comprehend who we are. People continue to lament language disappearing despite its widespread use in human life, since many people have died and others are in danger. Only a small number of the questions that were meant to be asked were actually asked. We attempted to examine key topics, including the significance of languages, language statistics, the actual source of the endangerment, and a solution. Even though the problem is somewhat broad, we made an effort to keep it as simple as possible so as not to mislead readers.